Unmasking the psychiatric impact of ketamine in burn patients: Elevated risk of depression and acute stress reactions: Psychiatric impact of ketamine in burn patients - Lee, Davon; Beyene, Elizabeth; Monroe, Da’Jhai; McMillan, Elijah; Lyles, Sierra; Creavalle, Marqus; Zelelew, Biniam; Gillani, Syed Fahad; Bisrat, Mekdem; Zinabu, Samrawit; Michael, Miriam (Journal of Surgery and Medicine, 2026)
Background/Aim: Ketamine is frequently administered for analgesia and sedation during burn dressing changes, but its potential psychological impact remains a concern. This study assessed whether ketamine exposure during early burn care is associated with subsequent depression, acute stress reaction (ASR), or post-traumatic stress disorder (PTSD) in patients with major burns. Methods: A retrospective cohort study was conducted using the TriNetX global health research network. Patients aged 12 to 90 years with burn injuries involving ≥10% total body surface area were included. Two cohorts were defined according to ketamine exposure within one month of injury. Propensity score matching (1:1) was performed for age, sex, and race, yielding 3,518 patients per group. Outcomes were evaluated over one year using diagnostic codes for depression, ASR, and PTSD. Analyses included risk estimates, odds ratios, Kaplan-Meier methods, and hazard ratios. Results: Ketamine exposure was associated with a higher risk of depression (4.9% vs. 3.8%; odds ratio 1.30; hazard ratio 1.24; P = 0.012) and ASR (2.0% vs. 0.8%; odds ratio 2.56; hazard ratio 2.41; P < 0.001). PTSD incidence was similar between cohorts (0.6% vs. 0.6%; odds ratio 1.03; hazard ratio 0.99; P = 0.952). Conclusion: In patients with major burns, ketamine exposure during early care was associated with increased risks of depression and ASR, but not PTSD. These findings support routine psychological screening and follow-up when ketamine is used for burn-related analgesia and sedation.